Prosedur Penyimpanan Arsip dalam Mendukung Tertib Administrasi pada Kantor Desa Sirnagalih - Fikri Maulana; Asep Dadan Suhendar (LPPM Akademi Manajemen Administrasi Yogyakarta, 2026)
Proper archive management is an important factor in supporting orderly administration at the village level. However, previous studies have focused more on archiving systems in educational institutions and large organisations, resulting in a practical knowledge gap regarding the implementation of archive storage procedures in village administrations with limited resources. This study aims to analyse the archival storage procedures at the Sirnagalih Village Office. The method used is a descriptive qualitative approach through observation and interviews. The results of the study show that the stages of checking, indexing, coding, sorting, storing, and retrieving have been implemented, but not optimally, due to the absence of standard classification and limited facilities. This study contributes an empirical description of village archival practices and recommendations for systematic improvements to increase administrative effectiveness.